Lie detection using photoplethysmogram (PPG) signal incorporating age and gender variability - Nur Amirah binti Shariff (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
This study proposed a photoplethysmogram (PPG) based lie detection technique for different group of age and gender. PPG device has been used widely in biomedical field due to its advantages such as low cost and small in size. However, lie detection using biomedical signals such as PPG is not well researched. In addition, signal obtained from different gender might vary and there is still less research done about polygraph with different age and gender. Hence, this study will propose a lie detection mechanism using PPG signal incorporating age and gender to overcome the limitations of current techniques. This study includes 20 subjects from various age category and gender group. PPG data was collected using Easy Pulse hardware after subjects undergoes a mock crime scenario in two conditions which are normal and lie conditions. Normal PPG signal was collected when the subjects were in a relaxing state where lie PPG signal was acquired when the subjects were participating in the Guilty Knowledge Test (GKT). After that, these PPG waveforms were filtered to minimize the noise in the signal. The filtered PPG data was extracted using two classification techniques in order to distinguish between normal and lie PPG signal incorporating age and gender group which are peak differences and Cardiod area differences. The result for age groups show that Group A (10-19 years old) obtained the highest average values of peak differences and Cardiod area differences as high as 156mV and 44884.25 unit2 respectively which indicates that they tend to lie more than other age groups. On the other hand, for gender factors, the results show that female obtained higher average values than male which are up to 126.4 mV for average peak difference and 40887.2 unit2 for average Cardiod area differences. This indicates that female tend to use deceptive behaviour more than male. The overall results obtained shows that PPG signal is a credible and reliable technique to be used in detecting lie incorporating age and gender variability.